Penetrating large retro-orbital foreign body -fishing sinker: removal via endoscopic transnasal approach - Asha'ari, Zamzil Amin; M Rajet, Khairul Azhar; Leman, Wan Ishlah (Japan International Cultural Exchange Foundation, 2017)
Objective: To report a rare penetrating large orbital foreign body case in a young man with normal vision and ocular movement, and discuss issues regarding best route of its removal. Design: Case report. Materials and Methods: A young man had an accident while fishing and ended up with a sinker penetrated into his right orbit. He has no loss of vision and normal ocular movement. X-ray and CT scan showed a 4 cm bullet shaped sinker in the inferior aspect of the medial wall of the right orbit. Results: The removal was successfully done via endoscopic opening of the posterior ethmoid air cells and creating an opening at the anterior wall of the sphenoid sinus to facilitate the removal transnasally. There was no short term and long term complications resulting from the surgery. Conclusion: Transnasal endoscopic approach should be considered for removal of any medially positioned orbital foreign bodies. This case highlights the importance of a multidisciplinary approach in the management of orbital foreign body and in deciding the best route of foreign body removal to limit potential complications.